CONCEPTUAL PRINCIPLES OF EDUCATION HUMANIZATION OF THE FUTURE ENVIRONMENTAL SPECIALISTS - Тимчук, І.; Погоріла, С. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2019)
The article substantiates conceptual principles of education humanization of ecology students in the process of their professional training, and determines its efficiency conditions, namely: formation of a higher education teacher personality, able to carry out training of future ecologists on a humanistic basis; ensuring the humanistic orientation of students’ learning content; adherence by teachers to pedagogically advisable humanistic principles and application of "environmentally - directed" teaching methods; humanization of relationship between teachers and future ecologists. There was substantiated the requirements system to a higher education teacher, among which special place is given to common civil features, moral and pedagogical qualities, individual psychological peculiarities and professional competence. The basic component of the teacher’s personality structure is his humanistic orientation, which is manifested in relation to a student as the highest value, recognition of his right to freedom and happiness, free development and manifestation of abilities. The authors proposed a provision on the example of teaching psychological cycle disciplines, based on ensuring humanistic orientation of the student learning content, aimed at the formation of a humanist-oriented personality of a specialist-ecologist with eco-centric type of ecological consciousness. There was carried out a characteristics of ecologically oriented teaching methods. They are the methods of forming ecological consciousness, thinking; education of ecological values; methods of forming subjective attitude to nature; methods of practical interaction with the natural world. Particular attention is paid to methods of forming a subjective attitude to nature (ecological identification, ecological empathy, ecological reflection), methods of practical interaction with the world of nature (field practices), methods of objective reality cognition at the level of ecosystems (observation in nature, ecological paths) , audio-visual methods and methods for predicting and demonstrating the possible consequences of destructive behavior. The authors pay attention to the application peculiarities of active forms of work and computer networks in the educational process, which will promote increased interest in learning, formation in students the independent work skills, will teach students to adapt to modern society requirements